ROLE OF ORTHODONTICS IN FORENSIC FACIAL RECONSTRUCTION FOR HUMAN IDENTIFICATION (Journal of Forensic Medicine & Toxicology, 2023)
Forensic science is the application of a wide range of scientific principles and techniques in thought to answer questions of interest relating to the fields of justice and law. Forensic odontology or dentistry has over the years become an intrinsic subject in the field of forensic medicine and this precise field has helped in the investigation and prosecution of crimes and criminals in many ways. The use of teeth for personal identity can yield important details such as orthodontic adjustments, dental prostheses and restorations, which remain throughout a person’s life and death and play an important role in personal identity. In cases where teeth have been useful in identifying unidentified deceased body, or bite-mark evaluation in cases of sexual assaults and child abuse or in self-defence or aggression, has the potential to reveal identity of the individual who left the bite mark at the time of offence. Orthopaedists can provide essential and important clues to investigating officers as they maintain proper dental records that contain important information that can help with personal identification.
Keywords: Orthodontics; Forensic dentistry; Bite marks; Teeth; Deceased; Personal identification